PENERAPAN METODE BRAINWRITING DALAM UPAYA MENINGKATKAN KETERAMPILAN MENULIS TEKS EKSPOSISI PADA SISWA KELAS X MM DI SMK 6 DENPASAR TAHUN AJARAN 2022/2023 - Ni Kadek Budi Hatiningsih; I Nyoman Suparsa; IGA Putu Tuti Indrawati (JIPBSI (Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia), 2023)
This research is a classroom action research (PTK) which aims to 1) test the effectiveness of the brainwriting method in improving the writing skills of exposition texts in class X MM students at SMK Negeri 6 Denpasar; 2) Knowing the steps of the brainwriting method in improving the skills of writing exposition texts in class X MM students at SMK Negeri 6 Denpasar; 3) Knowing the student's response after applying the brainwriting method. Data collection was carried out using observation, tests andquestionnaires. The data that has been obtained was analyzed using a qualitative descriptive technique. The research results obtained showed that after applying the brainwriting method there was an increase in the skills of writing exposition texts in class X MM students at SMK Negeri 6 Denpasar. The improvement in writing skills of exposition texts can be seen from the results of the students' average scores obtained in the first cycle test, which was 74.88 and increased in the second cycle, which was 82.43. The level of application of the brainwriting method has obtained maximum results. The results of the student response questionnaire that the brainwriting method can improve learning achievement. This can be seen from the ability of students who are more confident to express ideas, thoughts and opinions better.